Antioxidant and anti‐inflammatory activities of ethyl acetate extracts of chub mackerel (Scomber colias): a thorough seasonal evaluation. (15th June 2021) - Cardoso, Carlos; Matos, Joana; Gomes‐Bispo, Ana; Afonso, Cláudia; Motta, Carla; Castanheira, Isabel; Prates, José A. M.; Bandarra, Narcisa M.
Summary: The seasonal variation of key bioactivities in ethyl acetate extracts of chub mackerel ( Scomber colias ), an underutilised fish species, was evaluated through a complete monthly sampling. The phenolic content had a seasonal variation, ranging from 39 ± 5 mg GAE/100 g ww (February) to 340 ± 6 mg GAE/100 g ww (October). Ferric reducing antioxidant power (FRAP) increased from 1.3 ± 0.4 μmol Fe 2+ Eq/g ww (January) to 10.3 ± 0.1 μmol Fe 2+ Eq/g ww (September). ABTS had no antioxidant activity between June and December, being the highest value in February, 64.3 ± 6.3 μmol Trolox Eq/100 g ww. For phenolic content and FRAP, there was a strong seasonality, which was similar to that of the lipid content. Therefore, correlations were high, being R 2 0.95 for lipid vs. phenolic contents. Anti‐inflammatory activity did not show large changes throughout most part of the year, remaining high in the 70–80% of COX‐2 inhibition. This finding and the seasonality of the antioxidant properties warrant further research. Abstract : Ethyl acetate extracts of chub mackerel (Scomber colias) display significant bioactivities, which vary in accordance to a seasonal pattern.